Penanganan Kejadian Atresia Ani pada Anak - Haryono Rudi (Jurnal Keperawatan Notokusumo, 2013)
Atresia ani is not complete embryonic development in the distal rectum or anus closed abnormally. Atresia ani have another name ie imperforate anus. If atresia occurs it is almost always requires surgery to create a channel like normal state. Data obtained atresia ani events arising in the ratio 1 of 5000 live births, with a population of 200 million and Indonesia 35 per mil birth rate, it is predicted to be born each year with the disease in 1400 infants atresia ani. Atresia Ani with basically any type need to be given attention to the effects that would be caused to the child afterwards. So early detection is very important to be done by a nurse or medical team who are competent in the field. The most appropriate time to detect genital abnormalities shortly after the baby is born. At least with a physical examination and digital rectal inspection. The main treatment is surgery with time and adjusted models of type or classification of atresia ani suffered. But the nursing actions that are based on the establishment of nursing diagnosis is also important to provide good care and treatment to sustain the elimination of basic human needs, both before and after surgery.